Cartographie des paysages : apport à l’analyse des trames vertes et bleues - Émilie Bourget; Laurence Le Dû-Blayo (Projets de Paysage)
Nowadays landscape Atlases cover a great part of mainland France. Beyond their great diversity they all try to describe landscape units of their territories. In order to clarify the situation, the French department of ecology and sustainable development defined a specific vocabulary to link landscape and scales of observation : landscape unit, landscape structure, landscape element. Remote sensing, linked with a land approach, allows identification and cartography of some differents landscape types, and therefore of the landscape structures, particularly with the object-oriented approach. This method is based on the classification of segmented objects extracted from a high-resolution satellite image. This study shows an example picked up on the Pays de Saint-Brieuc, in Côtes d’Armor (France), and deals specifically with the case of the valleys, which strongly structure this space.